Comparison of Safety Margins and Airway Performance Between Air-Q And I-Gel as Conduits for Microcuff Endotracheal Tube Placement in Pediatric Surgeries: A Randomized Interventional Study - Pratibha Rathore; Ritesh Kumar Sompura; Neelam Dogra; Rama Chatterjee; Ram Kishan Vyas; Harshita Rai (Faculty of Medicine-Universitas Airlangga, 2026)
Introduction: Supraglottic airway devices (SADs) play a crucial role as conduits for blind endotracheal intubation, bridging ventilation, and intubation. This study aimed to compare the safety margins of Air-Q and I-Gel devices when used as conduits for Microcuff endotracheal tube placement in pediatric patients, utilizing both in vivo and in vitro assessments. Objective: This study aimed to compare the safety margin between Air-Q and I-Gel supraglottic airway devices when used as conduits for Microcuff endotracheal tube placement in pediatric patients, and to evaluate secondary outcomes including fiberoptic grade of view, oropharyngeal leak pressure at specified intervals, and intraoperative haemodynamic changes. Methods: After ethics committee clearance and informed consent, 60 children aged 5-10 years, weighing 13-38 kg, of American Society of Anesthesiologists grade I and II, posted for elective surgeries, were randomly allocated into two groups, Air-Q and I-Gel. Study parameters assessed. Statistical analysis involved independent sample t-tests and chi-square tests (significant p-value < 0.05). Results: Demographic parameters were comparable in both groups. Both devices were successfully inserted in all patients. The safety margin (cm) was significantly higher in the Air-Q group compared to the I-Gel group for the largest endotracheal tube (ETT) (7.6 ± 0.91 vs. 5.91 ± 0.52; p<0.001), one size small ETT (6 ± 0.42 vs. 4.36 ± 0.73; p<0.001), and two sizes small ETT (4.7 ± 0.84 vs. 3.16 ± 1.19; p<0.001). The fiberoptic grades of view were significantly better in the Air-Q group (p<0.001). In contrast, the mean OLP was significantly higher in the I-Gel group immediately (18.57±1.59 vs. 24.1±1.49, p<0.001) and 10 minutes post-insertion of the devices (25.7±1.88 vs. 31.1±1.9, p<0.001). Conclusion: The Air-Q group demonstrated a better safety margin than the I-Gel group; both devices were well-tolerated intubating conduits. A larger safety margin with Air-Q may reduce the risk of cuff-related laryngeal injury and accidental extubation during SAD removal.